2012
DOI: 10.1097/brs.0b013e31824ee623
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Discectomy and Fusion Versus Cervical Disc Arthroplasty

Abstract: Patients undergoing CDA tended to be younger and to have less comorbidity, shorter hospital stays, and lower costs. The number of CDAs increased over time, although the percentage remained relatively small in comparison with that for ACDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Further emphasizing the importance of this evidence gap is the overall increasing annual volume of ACDF procedures 1 and the increasingly comorbid population undergoing these surgeries. 11 Moreover, with emerging reports encouraging outpatient ACDF, 12 it is important to identify subgroups at risk for perioperative emergent reintubation to mitigate catastrophic complications after discharge.…”
Section: Résumémentioning
confidence: 99%
“…Further emphasizing the importance of this evidence gap is the overall increasing annual volume of ACDF procedures 1 and the increasingly comorbid population undergoing these surgeries. 11 Moreover, with emerging reports encouraging outpatient ACDF, 12 it is important to identify subgroups at risk for perioperative emergent reintubation to mitigate catastrophic complications after discharge.…”
Section: Résumémentioning
confidence: 99%
“…[68][69][70] Nevertheless, recent studies have demonstrated an increased rate of CDA use for similar pathologies. [71][72][73][74][75][76] In a retrospective review of a nationwide inpatient sample, Nesterenko et al observed an estimated 700% increase in CDA cases performed from 2005 to 2008 (344 to 2434). 76 increase was after 2013, likely secondary to more devices being approved after this date.…”
Section: Overall Trends and Costs Of Acdf And Cdamentioning
confidence: 99%
“…[71][72][73][74][75][76] In a retrospective review of a nationwide inpatient sample, Nesterenko et al observed an estimated 700% increase in CDA cases performed from 2005 to 2008 (344 to 2434). 76 increase was after 2013, likely secondary to more devices being approved after this date. 75 Cost comparisons between these two interventions has also changed over time.…”
Section: Overall Trends and Costs Of Acdf And Cdamentioning
confidence: 99%
“… 4 , 5 Consequently, the artificial disc has been developed as an alternative to provide the mobility of the instrumented segments and decrease the compensated mobility to the adjacent segments. 6 , 7 The hybrid use of ACDF and cervical artificial disc replacement (C-ADR) has also been adopted to treat the multilevel instability and degeneration of the cervico-thoracic column. 8 11 Theoretically, there are 4 strategies of two-level instrumentation to place the peek cage (P) and artificial disc (A): PP, AA, PA, and AP.…”
Section: Introductionmentioning
confidence: 99%